ON THE DIVERGENCE OF WALSH AND HAAR SERIES BY SECTORIAL AND TRIANGULAR REGIONS - Karagulyan, G.A.; Muradyan, K.R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
Almost everywhere (a.e.) divergence problems of the triangular and sectorial partial sums of the double Fourier series in Walsh and Haar orthonormal systems are studied. In particular, is constructed an example of bounded function on the unit square, which double Walsh–Fourier series diverges a.e. by an increasing sequence of triangular regions.
Keywords: Haar series, Walsh series, divergence of triangular sums, divergence of sectorial sums